A Spanish Validation of the Canadian Adolescent Gambling Inventory (CAGI) - Jiménez-Murcia, Susana; Granero, Roser; Stinchfield, Randy; Tremblay, Joël; del Pino-Gutiérrez, Amparo; Moragas, Laura; Savvidou, Lamprini G.; Fernández-Aranda, Fernando; Aymamí, Neus; Gómez-Peña, Mónica; Tárrega, Salomé; Gunnard, Katarina; et al. (Frontiers in Psychology, 2017)
Aims. Large-scale epidemiological studies show a significant prevalence of gambling disorder (GD) during adolescence and emerging adulthood, and highlight the need to identify gambling-related behaviors at early ages. However, there are only a handful of screening instruments for this population and many studies measuring youth gambling problems use adult instruments that may not be developmentally appropriate. The aim of this study was to validate a Spanish version of the Canadian Adolescent Gambling Inventory (CAGI) among late adolescent and young adults and to explore its psychometric properties. Methods. The sample (16-29 years-old) included a clinical group (n=55) with gambling disorder (GD) patients and a control group (n=340). Results. Exploratory factor analysis yielded one factor as the best model. This 24-item scale demonstrated satisfactory reliability (internal consistency, Cronbach’s alpha, =0.91), satisfactory convergent validity as measured by correlation with SOGS (r=.74), and excellent classification accuracy (AUC=0.99; sensitivity=.98; and specificity=.99). Conclusions. Our results provide empirical support for our validation of the Spanish version of the CAGI. We uphold that the Spanish CAGI can be used as a brief, reliable and valid instrument to assess gambling problems in Spanish youth.